Introducing ocean energy industries to a busy marine environment. (July 2017) - Hammar, Linus; Gullström, Martin; Dahlgren, Thomas G.; Asplund, Maria E.; Goncalves, Ines Braga; Molander, Sverker
Abstract: The immense energy potential of the oceans is being increasingly recognized the world over, at the same time the integrity of marine ecosystems is challenged by pressure from multiple human activities. For good reasons environmental licensing procedures are precautionary and new industries must declare their detrimental impacts and provide mitigation measures. New ocean energy industries target renewable energy sources thus, on a grand scale, partly mitigating climate change. However, on-site environmental impacts are yet to be established. In this review we compare ocean energy industries with a wide range of conventional, better understood, human activities and outline environmental risks and research priorities. Results show that ocean energy systems are thought to incur many pressures, some familiar and others with yet unknown effects. Particular uncertainties regard ocean thermal energy conversion (OTEC) and large fast-moving turbines. Ocean energy industries should not be considered in isolation because the significance of environmental impacts depend on the full spectra of human activities in each area. Marine spatial planning provides a platform for holistic assessments and may facilitate the establishment of ocean energy industries, as long as risk-related uncertainties are reduced.